Ozone sensitivity assessment of ’Pedro Sato’ guava - Moraes, Regina Maria; Furlan, Claudia Maria; Meirelles, Sergio Tadeu; dos Santos, Deborah Yara Alves Cursino; de Souza, Silvia Ribeiro; Viola, Sandra Regina de Araújo da Silva; de Rezende, Fernanda Mendes; Barbosa, Joyce Marques; Domingos, Robson Lazareti (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the sensitivity of 'Pedro Sato' guava to ozone (O3), in comparison to the cultivar Paluma, considered sensitive. Eight plants of each cultivar were subjected separately to filtered air and filtered air + O3 five hours per day, for four days. Photosynthesis (Asat), visible foliar injuries, and concentration of anthocyanin and tannin were evaluated. Plants of both cultivars were also exposed, during three months, to environmental conditions at a site polluted by O3, and growth, photosynthesis, and injuries were evaluated. Plants fumigated with O3 showed reduction of Asat and photochemical activity, besides foliar injury expression. 'Paluma' showed greater reduction of Asat, severe foliar injury and tannin reduction. When exposed to the polluted environmental conditions, 'Paluma' had higher gas exchange, but showed Asatt decrease 30 days before 'Pedro Sato'. Growth was not affected in 'Pedro Sato', whose foliar injuries had lower incidence, severity, and precocity than in 'Paluma'. The lower growth rate of 'Paluma' indicates greater O3 sensitivity. Although the cultivar Pedro Sato responded with less intensity to ozone-induced stress, it cannot be considered tolerant, since it is susceptible to photochemical damage, foliar injuries, and alterations in secondary metabolite content when exposed to this contaminant.